Benzimidazole derivatives protect against cytokine-induced apoptosis in pancreatic β-Cells. Issue 20 (15th October 2015) - Zawawi, Nik Khairunissa Nik Abdullah; Rajput, Sajid Ali; Taha, Muhammad; Ahmat, Norizan; Ismail, Nor Hadiani; Abdullah, Noraishah; Khan, Khalid Mohammed; Choudhary, M. Iqbal
Graphical abstract